(untitled) (Journal of Hama University, 2026)
This research aims to identify and determine the impact of the expert’s mantle strategy on developing some of the life skills among fourth grade students among a sample of (54) male and female learners, It was distributed into two groups, experimental and control. In order to achieve the objectives of the research, a quasi-experimental approach was used through the researcher applying to the experimental group an educational program based on the Mantle of the Expert strategy, while the usual method was applied to the control group, and a life skills test was prepared. The research reached results. The following: There are statistically significant differences at the level of significance (0.05) between the average scores of the learners of the experimental and control groups in the life skills test, in favor of the experimental group, and the presence of statistically significant differences between the average scores of the learners of the experimental and control groups in the pre- and post-applications of the life skills test, and these differences were in favor of the application. Al-Baadi, There is an impact of the expert’s mantle strategy on learning social studies, and the researcher suggested the necessity of using the expert’s mantle strategy in teaching social studies and training teachers on it.